Global fixed-time adaptive fuzzy path following control for unmanned surface vehicles subject to lumped uncertainties and actuator saturation - Fan, Yunsheng; Shi, Yanpeng; Mu, Dongdong; Liu, Jiaxian; Li, Zhihao (Ocean engineering, 2023)
A global fixed-time control strategy is presented for addressing the path following problem of underactuated unmanned surface vehicles (USVs) with lumped uncertainties and actuator saturation in this paper. Firstly, a novel fixed-time dual adaptive line-of-sight (FTDALOS) guidance law is proposed, which provides the desired heading angle and surge velocity. Subsequently, considering the complex marine environment, a novel fixed-time adaptive fuzzy controller (FTAFC) is developed. Additionally, to solve the issues of lumped uncertainties and actuator saturation, a fixed-time adaptive fuzzy control strategy and a fixed-time dynamic auxiliary saturation system are proposed. It is demonstrated that the proposed strategy can drive the USV along the desired path smoothly and rapidly, and all errors of the closed-loop system can converge to arbitrary small neighborhoods of the origin within fixed-time intervals. Finally, the effectiveness and superiority of FTDALOS guidance law and FTAFC are verified by theoretical analysis and simulation studies. •A global fixed-time control strategy for path following of USV is proposed.•A novel fixed-time dual adaptive line-of sight guidance law is created.•A novel fixed-time adaptive controller is designed to improve the robustness.•The influence of lumped unknowns is reduced by fixed-time adaptive fuzzy strategy.•Actuator saturation problem is solved by fixed-time auxiliary saturation system.